2010
DOI: 10.1016/j.bbrc.2010.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Functional dominant-negative mutation of sodium channel subunit gene SCN3B associated with atrial fibrillation in a Chinese GeneID population

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia in the clinic, and accounts for more than 15% of strokes. Mutations in cardiac sodium channel α, β1 and β2 subunit genes (SCN5A, SCN1B, and SCN2B) have been identified in AF patients. We hypothesize that mutations in the sodium channel β3 subunit gene SCN3B are also associated with AF. To test this hypothesis, we carried out a large scale sequencing analysis of all coding exons and exon-intron boundaries of SCN3B in 477 AF patients (28.5% lone AF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 25 publications
(41 reference statements)
1
50
0
Order By: Relevance
“…Watanabe et al 70 found two nonsynonymous loss-of-function mutations in SCN1B and two in SCN2B in a cohort of 480 AF patients. Wang et al 71 found a lossof-function mutation in SCN3B in another lone AF cohort. Moreover, Olesen et al 72 identified three non-synonymous mutations in SCN3B, which displayed a loss-of-function effect in the sodium current.…”
Section: Sodium Channel Mutationsmentioning
confidence: 95%
“…Watanabe et al 70 found two nonsynonymous loss-of-function mutations in SCN1B and two in SCN2B in a cohort of 480 AF patients. Wang et al 71 found a lossof-function mutation in SCN3B in another lone AF cohort. Moreover, Olesen et al 72 identified three non-synonymous mutations in SCN3B, which displayed a loss-of-function effect in the sodium current.…”
Section: Sodium Channel Mutationsmentioning
confidence: 95%
“…Genome-wide linkage analysis with polymorphic genetic markers mapped multiple susceptibility loci for AF on human chromosomes 10q22, 6q14-16, 11p15.5, 5p13, 10p11-q21 and 5p15, of which AF-causing mutations in 2 genes, KCNQ1 on chromosome 11p15.5 and NUP155 on chromosome 5p13, were identified and functionally characterized (15)(16)(17)(18)(19)(20)(21). Additionally, a genetic scan of candidate genes revealed a long list of AF associated genes, including KCNE2, KCNE3, KCNE5, KCNH2, KCNJ2, KCNA5, SCN5A, SCN1B, SCN2B, SCN3B, NPPA, GJA1 and GJA5 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Nevertheless, AF is a genetically heterogeneous disease and the genetic determinants for AF in a large proportion of patients remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, Wang and colleagues sequenced 477 patients with AF for mutations in SCN3B and identified a missense mutation in SCN3B (c.389CϾT resulting in p.A130V, located in the distal portion of the amino terminus) in one patient. 49 When coexpressed with Na v 1.5, the mutant ␤3-subunit resulted in a decrease in peak I Na density and no gating changes. Surprisingly, Western blot analysis revealed that the mutation did not affect the surface expression of Na v 1.5.…”
Section: Wilde and Brugada Cardiac Disease And Subunits Of The Sodiummentioning
confidence: 99%
“…46 In addition, mutations in the ␤-subunits SCN1B, SCN2B, and SCN3B have been associated with AF by decreasing I Na . [47][48][49] It is hypothesized that loss of I Na function leads to altered atrial conduction parameters, increased fibrosis, and associated structural abnormalities (including increased diastolic ventricular pressure in the setting of dilated cardiomyopathy with subsequent enlargement of the atria), that all act together to cause AF. …”
mentioning
confidence: 99%